Effectiveness of farmer groups as tools of extension service delivery : The case of Makhuduthamaga-Sekhukhune (Limpopo Province) - Harry, Mashiane Papie ([Bloemfontein?] : Central University of Technology, Free State, 2012)
Small-scale and subsistence farmers in general lack knowledge and information as a result of limited personal contact at grassroots level with extension workers. Therefore, the formation of farmer groups needs to be encouraged in most rural areas as tools of extension delivery. The value of farmer groups for quality decision making and generating of new ideas is well known, and therefore, the use of group contact may accelerate capacity building and empowerment to subsistence farmers. The problem under investigation is the effectiveness of farmer groups as tools of extension delivery in Makhuduthamaga in Sekhukhune District. The investigation seeks to establish the factors that influence the effectiveness of the farmer group in Makhuduthamaga local municipality. This study was conducted in the Makhuduthamaga local municipality in Sekhukhune District. Data was gathered through two questionnaires, one for farmers and one for extension workers. The study applied quantitative methodology, cluster sampling and non-probability sampling methods, and used field interviews with structured questionnaires. The study found that there are many stakeholders involved in the formation of farmer groups, such as NGOs, social welfare and extension workers, and the initiation by the different stakeholders has an influence on the development of the groups. Most of the farmer groups were initiated by NGOs, the reason being the financial support offered. The effectiveness of the selected farmer groups on Makhuduthamaga municipality is influenced by group dynamic factors. These factors include group size and gender composition, updating of the constitution, and the frequency of group meetings. The respondents highlighted the fact that there is a poor relationship within the groups, poor leadership, misuse of funds, lack of knowledge and division in the groups. There is a culture of not believing and/or not trusting the local people, and it is difficult to disclose information. The number of extension workers is still small in relation to the size of the farming population to be served. Stakeholders will learn from the study that the formation of farmer groups should serve the interests of the farmers, not of the institutions. The training institutions should base the training of extension workers on the needs of the farmers. The farmers should strive for self-reliance in order to sustain their farming enterprises. Extension workers should be formally trained on group dynamics, because agriculture in rural areas is about people working together. Government should minimise the top down approach and institutionalise the participatory extension approach methodology.
Thesis (M. Tech. Agriculture) -- Central University of Technology, Free state, 2012
Keywords: Central University of Technology, Free State - Dissertations; Agricultural extension work - South Africa - Sekhukhuneland; Non-governmental organizations - South Africa - Sekhukhuneland; Agricultural education; Agricultural extension workers - South Africa - Sekhukhuneland - Societies, etc.; Dissertations, academic - South Africa - Bloemfontein